HUBUNGAN KOMUNIKASI TERAPEUTIK, WAKTU TUNGGU DAN KUALITAS PELAYANAN DENGAN KEPUASAN PASIEN DI KLINIK ASY-SYIFA KUDUS - Mukti, Muhammad Haykal Candra; Rusnoto, Rusnoto; Suwandi, Edi Wibowo (Universitas Pesantren Tinggi Darul Ulum, 2025)
This study aims to analyze the relationship between therapeutic communication, waiting time, and service quality to patient satisfaction at Asy-Syfa Clinic Kudus. Patient satisfaction is an important indicator in assessing the quality of health services. Factors such as good therapeutic communication, efficient waiting time, and optimal service quality are believed to have a significant role in increasing patient satisfaction. This study used a descriptive correlational design with a cross-sectional approach, involving 97 patients selected using accidental sampling techniques. Data were collected through questionnaires and analyzed using the Spearman rank test. The results of this study are expected to provide strategic recommendations for Asy-Syfa Clinic to improve service quality, optimize waiting time management, and improve the quality of therapeutic communication so as to increase overall patient satisfaction. Keywords: communication, waiting time, service quality, patient satisfaction